해양부이 자료를 이용한 황해 남동부 해역 표층 열속 산출 - 김선복; 장경일; Kim, Sun-Bok; Chang, Kyung-Il (Pada (Hanʼguk Haeyang Hakhoe), 2014)
Monthly mean surface heat fluxes in the southeastern Yellow Sea are calculated using directly observed airsea variables from an ocean buoy station including short- and longwave radiations, and COARE 3.0 bulk flux algorithm. The calculated monthly mean heat fluxes are then compared with previous estimates of climatological monthly mean surface heat fluxes near the buoy location. Sea surface receives heat through net shortwave radiation ($Q_i$) and loses heat as net longwave radiation ($Q_b$), sensible heat flux ($Q_h$), and latent heat flux ($Q_e$). $Q_e$ is the largest contribution to the total heat loss of about 51 %, and $Q_b$ and $Q_h$ account for 34% and 15% of the total heat loss, respectively. Net heat flux ($Q_n$) shows maximum in May ($191.4W/m^2$) when $Q_i$ shows its annual maximum, and minimum in December ($-264.9W/m^2$) when the heat loss terms show their annual minimum values. Annual mean $Q_n$ is estimated to be $1.9W/m^2$, which is negligibly small considering instrument errors (maximum of ${±}19.7W/m^2$). In the previous estimates, summertime incoming radiations ($Q_i$) are underestimated by about $10{\sim}40W/m^2$, and wintertime heat losses due to $Q_e$ and $Q_h$ are overestimated by about $50W/m^2$ and $30{\sim}70W/m^2$, respectively. Consequently, as compared to $Q_n$ from the present study, the amount of net heat gain during the period of net oceanic heat gain between April and August is underestimated, while the ocean's net heat loss in winter is overestimated in other studies. The difference in $Q_n$ is as large as $70{\sim}130W/m^2$ in December and January. Analysis of long-term reanalysis product (MERRA) indicates that the difference in the monthly mean heat fluxes between the present and previous studies is not due to the temporal variability of fluxes but due to inaccurate data used for the calculation of the heat fluxes. This study suggests that caution should be exercised in using the climatological monthly mean surface heat fluxes documented previously for various research and numerical modeling purposes. 황해 남동부 해역에 설치한 해양부이(YSROB)에서 약 27개월간 관측된 장파, 단파 복사량을 포함한 대기, 해양 변수와 COARE 3.0 알고리즘을 이용하여 월평균 해양-대기간 열속을 산출하고 기존 연구결과와 비교하였다. YSROB 위치에서 열속은 순 단파복사(Qi)에 의해 해양은 대기로부터 열을 얻고 순 장파복사($Q_b$), 현열($Q_h$), 잠열($Q_e$)에 의해서 열손실이 일어난다. 전체 열손실 중 $Q_e$에 의한 손실이 51%로 가장 크게 나타났으며 $Q_b$와 $Q_h$에 의한 손실은 각각 34%, 15% 이다. 순열속($Q_n$)은 $Q_i$가 최대인 5월에 최대($191.4W/m^2$)이며 모든 열속 성분이 최소인 12월에 최소($-264.9W/m^2$)이다. 연평균 $Q_n$은 $1.9W/m^2$ 이지만 관측기기의 정확도에 의한 오차산정 결과(최대 ${±}19.7W/m^2$)를 고려하면 무시할 정도로 작다. YSROB과 동일한 위치에서의 기존 월별 열속 산출 결과는 YSROB에서 실측값에 기반한 열속에 비해 여름철 $Q_i$가 약 $10{\sim}40W/m^2$ 과소 평가된 반면에 겨울철에는 $Q_e$와 $Q_h$에 의한 열 손실이 각각 약 $50W/m^2$, $30{\sim}70W/m^2$ 과다하게 산출되었다. 이로 인하여 해양이 열을 얻는 4월~8월에는 기존 연구에서의 열 획득량이 본 연구 결과보다 적게 나타나며, 해양이 열을 잃는 겨울철에는 기존 연구에서의 해양으로부터의 열 손실이 본 연구 결과에 비해 크게 나타난다. 특히, 12월과 1월의 $Q_n$ 차이는 약 $70{\sim}130W/m^2$에 달한다. 장기적인 재분석장(MERRA) 분석 결과에 의하면 이와 같은 월평균 열속의 차이는 연변동 등 시간 변동에 의한 것이 아니라 열속 산출 시 사용된 자료의 부정확성에 기인하는 것으로 판단된다. 본 연구 결과로부터 기존의 기후적인 열속을 연구에 활용하거나 수치모델에 사용함에 있어 주의가 요망된다.